Using bone bioapatite yield for quality control in stable isotope analysis applications. (February 2021) - Chesson, Lesley A.; Beasley, Melanie M.; Bartelink, Eric J.; Jans, Miranda M.E.; Berg, Gregory E.
Highlights: This study investigated bone bioapatite yield as a sample quality indicator. Bioapatite yield of modern skeletal remains ranged from 21% to 63%. In comparison, prehistoric bone in the best condition had yields of 29–62%. Prehistoric samples in poor condition had significantly higher bioapatite yields. Modern samples provided yield limits for bone prepared for stable isotope analysis. Abstract: Since the late 1970s, stable isotope analysis of bone has become a routine method in archaeological science for reconstructing an individual's life history. There is published guidance for assessing bone quality prior to stable isotope analysis, including measurement of bioapatite molecular structure, collagen yield, and collagen element content. This study investigated bioapatite yield as an additional quality indicator. Bioapatite and collagen were extracted from 182 modern (20th Century) and 272 prehistoric (5420–230 cal BP) human skeletal elements. As expected, modern remains were well-preserved, with ranges of 3–28% for collagen yield and 3.1–3.4 for the atomic carbon-to-nitrogen (C:N) ratio; bioapatite yield ranged from 21% to 63%. There was a significant, but only fair, negative correlation between bioapatite and collagen yields of modern samples ( r = -0.31, p < 0.0001). Conversely, no correlation was observed between bioapatite and collagen yields of prehistoric samples, suggesting preservation of one is not indicative of preservation of the other. Prehistoric sample condition was evaluated by measuring the infrared splitting factor (IR-SF) to evaluate bioapatite crystallinity and the carbonate-to-phosphate (C/P) ratio to measure carbonate concentration; yield and C:N ratio were used to evaluate collagen condition. Prehistoric samples in the best condition had bioapatite yields between 29% and 62%, within the range of modern samples. In contrast, prehistoric samples in poor condition had significantly higher bioapatite yields, suggesting diagenetic addition of material. The range of bioapatite yields from modern bone samples, 21–63%, is proposed as the least conservative acceptable threshold for screening bone prepared for stable isotope analysis.